IDENTIFICATION AND CHARACTERIZATION OF BACTERIAL SPECIES ISOLATED FROM CONTAMINATED BURN WOUNDS IN DISTRICT D.I.KHAN - Amina Abid; Nasreen Saif; Tauseef ul Hassan; Rahila Bano (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
A burn is an injury to the skin or other physiological tissues caused by several factors, including thermal injury, scalds, fire, electrical shock, and chemical exposure. The aims of the present study were to isolate, identify, and evaluate the sensitivity of bacteria isolated from burn-infected patients in District D.I. Khan to antibiotics. One hundred seven swab samples were collected from one hundred seven patients suffering from burn illnesses. Four unique bacterial isolates were identified based on colony morphology and biochemical testing, including oxidase, catalase, coagulase, indole, and motility: Pseudomonas aeruginosa, Klebsiella, Staphylococcus aureus, and Escherichia coli. The frequency distribution was as follows: Pseudomonas aeruginosa (71.43%), Klebsiella (14.29%), Staphylococcus aureus (10%), and Escherichia coli (4.3%). The predominant survey replies originated from persons aged 26-45 years, accounting for 45%, closely followed by respondents aged 11-25 years. Female infections comprised 65.42%, whereas male infections were 34.58%. A total of ten medicines were assessed, with levofloxacin and ciprofloxacin exhibiting enhanced efficacy. Moderate resistance to Amikacin, Chloramphenicol, and Gentamicin is observed. Imipenem, Amoxicillin, and Ceftriaxone were found to be less efficacious. Vigilance and diligence are crucial to avert infection in burn patients at District D.I. Khan. A comprehensive and meticulous study is necessary to avert or alleviate these disorders.